On Defining and Measuring the Informal Sector: Evidence from Brazil - Henley, Andrew; Arabsheibani, G. Reza; Carneiro, Francisco G. (2012)
Recent debate on the reasons for the informal sector has led to renewed focus on how to operationalize the measurement of informal employment. This paper investigates congruence between three empirical measures of the rate of informality using Brazilian household survey data for the period 1992-2004. Sixty-three percent of the economically active are informal according to at least one definition, but only 40% are informal according to all three. Regression analysis is used to shed further light on differences in these measures. Appropriate measurement is therefore of high significance to policy analysis and design of appropriate strategies to reduce informality.